A Survey on Marketing Potential of Maize Seed Production in the Western Hill of Nepal - Joshi, KR (Nepal Agriculture Research Journal, 2009)
A Marketing Rural Rapid Appraisal Survey (MRRA) was conducted from 12-16 June 2002 in Bhakimli (1725 masl), Myagdi district. Two factors namely gender (male and female) and wealth category rich, medium and poor were considered in accessible area of Bhakimli. Semi-structured questionnaires and checklist were used to collect information on maize seed production, marketing opportunities and marketing system for producers, traders and consumers. The objectives of the study were to understand existing maize seed production, demand and supply; to identify the problems associated with the seed marketing system and policy options for sustainable maize seed production. Farmers groups in Bhakimli were involved in maize seed production and management of marketing. Successful seed production for long-term would ensure a continuous supply of open pollinated variety (OPV) seed in farmers' level. Seed production as a new commercial enterprise created employment opportunities as well as income generating in the Western hills of Nepal. Keywords: Commercial enterprises; community seed production; employment; income generating; marketing potential DOI: 10.3126/narj.v7i0.1873 Nepal Agriculture Research Journal Vol.7 2006 pp.82-87